Pengaruh Ekstrakurikuler Angklung Terhadap Kecerdasan Musikal Anak Usia Dini - Wardani, Herfina; Putri, Mellysa; Sugiyarti, Dian; Afsanti, Isma; Utami, Novianti Retno (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
This study aims to examine the influence of angklung extracurricular activities on the musical intelligence of early childhood. It adopts an experimental research design with a pretest-posttest one-group design method, which allows for the evaluation of changes in musical intelligence before and after participation in the angklung activities. The research was conducted at TK BAIK Yogyakarta, involving 27 children aged 5-6 years in class B, ensuring a focused and specific demographic. Saturation sampling was chosen as the sampling technique, ensuring that all eligible participants from the population were included in the study. Data collection involved the utilization of a musical intelligence test instrument, carefully selected to measure the desired constructs effectively. The collected data were analyzed using descriptive statistics, providing a comprehensive overview of the participants' musical intelligence levels. The research findings revealed a significant increase in musical intelligence, as evidenced by the difference between the average pretest score of 79.85 and the posttest score of 84.96, with a difference of 5.11 points. This disparity underscores the positive impact of angklung extracurricular activities on enhancing the musical intelligence of 5-6-year-old children. The implications of this study suggest that incorporating angklung extracurricular activities into early childhood education programs can serve as a valuable approach for fostering musical intelligence development in young learners.